USE OF PIDGIN LANGUAGE IN COMMUNITY CONVERSATIONS SOUTH KOREA - Agus Sulaeman (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2023)
The purpose of this study is to describe the pidgin language of the people of South Korea by looking at the pidgin in Korean which was formed through the background of Japanese colonial history and Korean colonial history. Similar to Indonesia and Malaysia, South Korea was also under Japanese colonial rule from 1910 to 1945. Against this historical background, Japanese expressions or Japanese writing methods in Korean society are very commonly used today. The use of Japanese expressions and methods can easily be found in legal sentences and official documents used by the government. The data in this study are the formation of a new language from several languages or pidginization. this type of research is qualitative research. Data collection techniques in this study used observation, interview and documentation techniques, in this study the method used was content analysis method. From the research results, it was found that the Pidginization Process in general is a simplification of language form. for example morphologically (word structure) and syntactically (grammatical structure), tolerance for phonological variations (pronunciation), reduction of a number of functions, and extensive borrowing of words from several languages.